HUBUNGAN ANTARA PROFIL BERAT ORGAN MANUSIA INDONESIA DENGAN UMUR, JENIS KELAMIN, PANJANG BADAN, DAN BERAT BADAN (STUDI DI RSUP Dr. HASAN SADIKIN BANDUNG TAHUN 2008-2012 - Yosiati, Naomi; Fitrasanti, Berlian I.; Syukriani, Yoni F. (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2012)
In forensic medicine organ weight is a standard to determine health status and supports the determination of the cause of death. This study is aimed to analyze the correlation between organ weight profiles and age, body length, body weight, and gender; and to analyze the factors that give influence most to organ weight. Data were taken from autopsy reports of Indonesian adults, from 2008 to 2012 in Dr. Hasan Sadikin Hospital Bandung. Results showed—all male organ weight are heavier than female (N=243; 174 male, 69 female). In male there are significant correlations (p <0.05) between age and the weight of heart, right lung, liver, right kidney, and left kidney; whereas in female it is only between age and heart weight. In male there is significant correlations between body length and the weight of cerebrum, heart, liver, right kidney, and left kidney; whereas in female there is no significant correlation shown. In male there is significant correlations between body weight and the weight of cerebrum, heart, liver, spleen, and left kidney; whereas in female it is between body weight and the weight of heart, right lung, and liver. Body weight is the most influential factor to the weight of cerebrum, heart, and liver; as body length to the weight of right lung, left lung, and spleen; and age to the weight of cerebellum, right kidney, and left kidney. It can be concluded that body weight, body length and age are influential to certain organs, each with different significance level
Keywords: organ weight; age; body length; body weight; anthropometry